Seroprevalence of Anaplasma phagocytophilum in dogs at Durán Guayas Province, Ecuador - Gavilanez Paredes, María José; Alava Anchala, Emily Margarita; Mendoza Castañeda, Georgia Elena (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2024)
The objective of this research study is to determine the seroprevalence of Anaplasma phagocytophilum in 30 domestic dogs, in two sectors belonging to the Durán canton. The first was located in the "El Edén Urbanization" and the second sampling in the "June 5 Cooperative". Method: We carried out brigades in both sectors, conducting surveys considering the variables of the study and evaluating which of the dogs was valid to perform the rapid immunochromatography test. Blood samples were obtained from canines and the blood test was run using the "VLabs 4LX" test, the test for the detection of Anaplasma phagocytophilum has a sensitivity of 94.59% and a specificity of 98.98%.  The result obtained from the first sector was a prevalence of 26.67% (4/15) and in the second sector from 6.67% (1/15).  As a total prevalence we obtained 16.66% (5/30) of the 30 dogs sampled. According to the other variables studied, such as age, external deworming and presence of the vector in the canines, it was established by means of the SPSS Software version 27 program that there is no association between the dependent variable and the independent variables. Conclusion: There is a high prevalence of Anaplasma phagocytophilum, a hemoparasite that seriously affects dogs and is usually an underdiagnosed disease despite being a zoonotic disease, therefore it is important to adequately inform and explain the use of the different prevention methods, and the correct maintenance in the environment in which pets live.
Keywords: Anaplasma phagocytophilum; blood test; prevalence; rapid test